2012
DOI: 10.1111/j.1524-4725.2012.02441.x
|View full text |Cite
|
Sign up to set email alerts
|

“Tram Track Effect” After Treatment of Acne Scars Using a Microneedling Device

Abstract: The authors have indicated no significant interest with commercial supporters.S kin needling or percutaneous collagen induction (PCI) suing a dermal rolling device (a needling tool) is an office procedure used for managing postacne scars. The treatment of postvaricella scars and postacne scars usually requires multiple sessions. We would hereby like to report the undesirable effect of "tram tracking" with the use of this microneedling technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 3 publications
0
23
0
1
Order By: Relevance
“…There is one previous similar report and it is thought to be due to larger needling device or strong pressure exerted while doing the procedure. 14 The limitations of our study were lack of control group, lack of blinded evaluator, and subjective way of evaluating acne scars.…”
Section: Discussionmentioning
confidence: 94%
“…There is one previous similar report and it is thought to be due to larger needling device or strong pressure exerted while doing the procedure. 14 The limitations of our study were lack of control group, lack of blinded evaluator, and subjective way of evaluating acne scars.…”
Section: Discussionmentioning
confidence: 94%
“…Included were nine prospective observational studies (Beretta et al, 2008, Dogra et al, 2014, Fabbrocini et al, 2009, Fabbrocini et al, 2014b, Garg and Baveja, 2014, Kang et al, 2009, Kim, 2008, Majid, 2009, Schwarz and Laaff, 2011), nine prospective controlled studies (Alam et al, 2014, Fabbrocini et al, 2011c, Gadkari and Nayak, 2014; Kofal et al, 2014; Leheta et al, 2011, Leheta et al, 2014a, Leheta et al, 2014b, Mohammed, 2013, Sharad, 2011), and one case report (Pahwa et al, 2012). Additionally, one prospective observational study likely contained patients with acne scarring (Aust et al, 2008a), but the method was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Skin needling is expected to cause temporary erythema, pain, a burning sensation, edema, bleeding, or a serous ooze resolving with crusting or scabbing (Alam et al, 2014, Beretta et al, 2008, Dogra et al, 2014, Fabbrocini et al, 2009, Fabbrocini et al, 2011c, Fabbrocini et al, 2014b, Leheta et al, 2011, Majid, 2009, Sharad, 2011). Bruising and hematomas are also expected, particularly over bony prominences (Dogra et al, 2014, Fabbrocini et al, 2014b, Schwarz and Laaff, 2011), The development of “tram trek” scarring was reported with 2-mm needles in one case report (Pahwa et al, 2012). This phenomenon also occurred in a study using 1.5-mm needles (Dogra et al, 2014), but not in a study using 2.5-mm needles (Gadkari and Nayak, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported infections with herpes simplex virus, which were successfully treated with acyclovir. 16,17 (Figure 1) ( Figure 2) ( i. When the microlesion is generated, a short circuit occurs in the PET that activates the Na+/ K/ ATPase Pumps.…”
Section: Mechanism Of Actionmentioning
confidence: 99%